TEACHERS THEORETICAL AND PRACTICAL PROBLEMS IN APPLYING PERFORMANCE ASSESMENT IN ENGLISH LANGUAGE CLASSROOM : ITS RELEVANT IMPLEMENTATION IN ENGLISH FOR TOURISM ASSESSMENT - Dewa Gede Ngurah Byomantara (JURNAL BISNIS HOSPITALITI, 2016)
Performance Assessment (hereafter PA) is not really new, hut it is still difficult to apply. The majority of English language teachers could not design tasks and scoring rubrics of PA well. This is a gap. Based on the theoretical and practical characteristics of PA, "What possible problems might the English language teachers face in applying PA? " Therefore, this article present Assessment-related Terms, The Importance of Assessment, Why PA, what Pa, Types of PA, designing PA, Reliability and Validity of PA, Performing Standards and Scoring Rubrics. The complexity of PA needs highly dedicated teachers, high cost, wider spaceand longer time. Since PA contains long, complex procedures, an English language teacher might face problems in designing, preparing rubric of scoring/marking, interpreting the students'works, making decisions, and being objective. Teachers must be aware of the importance of personality building in relation to the application of PA.